IMPORTANCE OF ASSISTIVE MOBILE APPLICATIONS FOR DYSLEXIC STUDENTS IN SAUDI ARABIA: Received: 17th May 2021; Revised: 27th July 2021, 28th September 2021; Accepted: 30th October 2021 - Allafi, Randa; Newbury, Paul (PUPIL: International Journal of Teaching, Education and Learning, 2021)
Worldwide, Education systems have been affected by Covid-19; therefore, mobile learning (M-learning) has become more important in supporting flexibility and availability, leading to a clear trend in the learning process for this significant and valuable society sector. Much research has been conducted to measure the benefits of using Mobile Applications for students in general and specifically for students with learning disabilities such as dyslexia. Although a significant amount of research has discussed M-learning with dyslexic students in multiple languages, it is considered in its initial stages in many other languages; especially in Arabic countries. Thus, it is worthy of investigating the gaps related to such matters. This paper focuses on developing a mobile application that aims to enhance Arabic dyslexic students' reading skills. This study includes dyslexic students in Saudi Arabia who are eight to ten years old. The preliminary results showed promising prospects in such contexts for mobile learning, especially for dyslexic students. Furthermore, students showed very positive attitudes towards the proposed mobile application, leading to better engagement with learning Arabic.